2003
DOI: 10.1051/0004-6361:20021732
|View full text |Cite
|
Sign up to set email alerts
|

An EUV Bright Point as seen by SUMER, CDS, MDI and EIT on-board SoHO

Abstract: Abstract. This paper presents the formation, evolution and decay of a coronal bright point via a spectroscopic analysis of its transition region counterpart and the evolution of the underlying magnetic bipole during 3 days of almost continuous observations. The data were obtained with various instruments on-board SoHO, including the SUMER spectrograph in the transition region line S  933.40 Å, CDS in the He  584.33, O  629.73 and Mg  368.06 Å lines, plus MDI and EIT. The existence of the coronal feature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
76
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 31 publications
7
76
0
1
Order By: Relevance
“…6. Similar small-scale/short-duration brightenings are also seen in bright points (Doyle et al 1998;Madjarska et al 2003).…”
Section: Intensity Variationssupporting
confidence: 68%
“…6. Similar small-scale/short-duration brightenings are also seen in bright points (Doyle et al 1998;Madjarska et al 2003).…”
Section: Intensity Variationssupporting
confidence: 68%
“…We know so far that 88% of X-ray BPs are associated with converging magnetic polarities (Webb et al 1993) and most of the BPs are related to cancelling magnetic features. Usually, one of the magnetic polarities involved is stronger than the other (Madjarska et al 2003) and after the full cancellation of the weaker polarity, the remnant one either joins the CH dominant polarity (if it is of the same sign), expanding the CH surface, or forms a new connection (closed magnetic field lines) which triggers contraction of the CH boundaries. This scenario will be tested by applying magnetic field extrapolation on Michelson Doppler Imager data in high-resolution mode for CH2 as well as new forthcoming data from SOT/Hinode.…”
Section: Discussionmentioning
confidence: 99%
“…Kahler & Moses (1990) studied Skylab X-ray images of a single EECH with a time resolution of 90 min to look for discrete changes of the CH boundaries. They found that X-ray bright points (BPs, small-scale loops in the quiet Sun and CHs, for details see Madjarska et al 2003) play an important role in both the expansion and contraction of the CH. For this study, a single coronal hole observed during the decreasing phase of the solar cycle activity was used.…”
Section: Introductionmentioning
confidence: 99%
“…A&A 526, A134 (2011) Habbal & Withbroe (1981), on the other hand, found evidence of variations of EUV emission in chromospheric, transition region and coronal lines, on timescales as short as 5.5 min (the cadence of their Skylab observations). Some work based on SOHO/CDS and SUMER spectroscopic observations to study XBPs at transition region temperatures followed (see e.g., Madjarska et al 2003;Ugarte-Urra 2004;Ugarte-Urra et al 2005).…”
Section: Introductionmentioning
confidence: 99%